2017
DOI: 10.1021/acs.jpca.7b05995
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Hydroxyl-Functionalized Protic Ammonium Carboxylate Ionic Liquids

Abstract: We performed classical molecular dynamics simulations to investigate the structure and dynamics of protic ionic liquids, 2-hydroxy ethylammonium acetate, ethylammonium hydroxyacetate, and 2-hydroxyethylammonium hydroxyacetate at ambient conditions. Structural properties such as density, radial distribution functions, spatial distribution functions, and structure factors have been calculated. Dynamic properties such as mean square displacements, as well as residence and hydrogen bond dynamics have also been cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 92 publications
3
30
0
Order By: Relevance
“…In general, we have a density corresponding to the liquid phase, the function g(r) still shows a certain ordering of the system, with its several layers of solvation. The results obtained showed a great deal of similarity in behaviour of ionic vs. fluids of the literature [9,10]. Analysing the radial function of the liquid in figure 2, we see different maxima, relative to the interaction between the selected atoms, and a considerable increase in some maxima relative to the thickness of solvation layer, are also presented.…”
Section: The Radial Distribution Function (Rdf) Between Nitrogen and supporting
confidence: 58%
“…In general, we have a density corresponding to the liquid phase, the function g(r) still shows a certain ordering of the system, with its several layers of solvation. The results obtained showed a great deal of similarity in behaviour of ionic vs. fluids of the literature [9,10]. Analysing the radial function of the liquid in figure 2, we see different maxima, relative to the interaction between the selected atoms, and a considerable increase in some maxima relative to the thickness of solvation layer, are also presented.…”
Section: The Radial Distribution Function (Rdf) Between Nitrogen and supporting
confidence: 58%
“…(II) Second Step: Ter-molecular mechanism (Crooks & Donnellan and Alper, 1989) (Thummuru and Mallik, 2017).…”
Section: Proposed Reaction Mechanismsmentioning
confidence: 99%
“…In one of our previous studies, we reported the structure and dynamics of hydroxyl-functionalized ILs. 45 We explored the effect of the inclusion of the hydroxyl group on cations, anions, and both. When the hydroxyl group was substituted on the cations, the dynamics became slow.…”
Section: Introductionmentioning
confidence: 99%